Effect of diet control and exercise on the lipid profile of obese men - Al-Zahrani, Saad S. (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is a major health problem which might contribute to many other problems such as heart disease and hypertension as well as diabetes due to abnormal lipid profile. The main objective of the current study was to compare the effectiveness of diet or treadmill exercise on normalizing the lipid profile of obese subjects. Methods: Forty women complaining from obesity was enrolled in this study and was randomly divided into 4 groups: control group: 10 obese women which don’t receive any thing, diet group: 10 obese women which received polysaturated fatty acid diet, exercise group: 10 obese women which received treadmill exercise for 30 minutes and lastly diet/exercise group: 10 obese women which received both diet and exercise. Measurement of weight, body mass index, and lipid profile for all groups was measured before and after 60 days of treatment intervention. Results: Diet and exercise should have a highly significant decrease of weight and body mass index and normalizing the lipid profile (p≤0.05) under the current situation used in this study. Conclusions: It was concluded that the combination of diet and exercise was highly effective in normalizing the lipid profile and overcoming obesity.